2008
DOI: 10.1007/s00128-008-9533-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Geochemical Evaluation of the Water Quality of River Adyar, India

Abstract: The River Adyar flows through the fault of south Chennai for about 50 Km and enters into the Bay of Bengal. This river is almost stagnant and do not carry enough water except during rainy season. Rapid industrialization and urbanization along the river course during 80s and 90s of last century has increased the pollution of the river water. The main objective of this study is to identify and assess the nature of pollution. In order to achieve this objective, necessary geochemical parameters were determined and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 3 publications
0
12
2
2
Order By: Relevance
“…In contrast, mean Cu concentration in pre-monsoon (0.21 mg L −1 ) and post-monsoon (0.08 mg L −1 ) falls within the USEPA, EU and WHO criterion for water quality. However, measured concentrations are higher to those reported in other studies (Venugopal et al 2009). Mn concentration (0-7.8 mg L −1 )…”
Section: Characterization and Comparison Of Physiochemical Parameterscontrasting
confidence: 54%
See 2 more Smart Citations
“…In contrast, mean Cu concentration in pre-monsoon (0.21 mg L −1 ) and post-monsoon (0.08 mg L −1 ) falls within the USEPA, EU and WHO criterion for water quality. However, measured concentrations are higher to those reported in other studies (Venugopal et al 2009). Mn concentration (0-7.8 mg L −1 )…”
Section: Characterization and Comparison Of Physiochemical Parameterscontrasting
confidence: 54%
“…Similarly, Zn concentration was also above USEPA criteria but lower to those of WHO guideline of drinking water quality. Zn concentration recorded in the current study was higher to those reported in other studies (Jaji et al 2007;Venugopal et al 2009;Zhou et al 2007). …”
Section: Characterization and Comparison Of Physiochemical Parameterscontrasting
confidence: 52%
See 1 more Smart Citation
“…River water studies have received wide attention due to the need to understand the weathering, hydrological, seasonal, and anthropogenic factors which influences the water quality (Venugopal et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The urban runoff water quality greatly affects the surface and groundwater quality, fishing, animal and bird life, agriculture production, etc. in India (Chattopadhyay et al 2005;Mujumdar 2008;Rao and Mamatha 2004;Sargaonkar 2006;Solaraj et al 2010;Patel et al 2012;Venugopal et al 2009;Zafar and Alappat 2005). Water pollution is a very serious problem in India, which is the second most populous nation in the world.…”
Section: Introductionmentioning
confidence: 99%